Analysis and thinking of failed Japanese ITO cases in China. (1st January 2012) - Chen, Yongqiang; Yang, Huansong; Hong, Libin
With the quick expansion of Japanese services' outsourcing, 65% of Japanese ITO projects are outsourced to China, among which, ITO projects account for a big share. Based on a failed case of Japan's ITO project, this paper makes an analysis on plans of project management, project tasks and human resources management. The purpose of this paper is to find out the frustrated reasons and improve outsourcing services. Hence, people are able to draw lessons from certain experiences to improve the success rate of Japan's ITO services in China.